Pengaruh Tunjangan Kinerja Terhadap Kinerja Pegawai Di Kantor Camat Kecamatan Sukaraja - Yolani, Lendra; Lorita, Evi; Saputra, Harius Eko (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to examine the effect of performance allowances on the performance of civil servants at the District Office of Sukaraja Subdistrict, Seluma Regency. A quantitative approach with a correlational method was employed. The independent variable in this study is performance allowance, while the dependent variable is employee performance. The sample consisted of 20 civil servants, selected using a saturated sampling technique. Data were collected through a validated and reliable questionnaire. The data were analyzed using descriptive statistics, Pearson Product Moment correlation, simple linear regression, and hypothesis testing through t-test, f-test, and coefficient of determination (r²). The results showed that performance allowance had no significant effect on employee performance. This is indicated by the correlation coefficient value of 0.337, which is lower than the r table (0.444), and the determination coefficient value of 0.113, meaning that performance allowance contributes only 11.3% to employee performance. Additionally, the t-count value (1.518) was lower than the t-table value (1.729), leading to the rejection of the alternative hypothesis. Thus, it can be concluded that performance allowances are not the main factor influencing employee performance at the Sukaraja Subdistrict Office.